2022
DOI: 10.1039/d2nr03676b
|View full text |Cite
|
Sign up to set email alerts
|

A dual gate-controlled intelligent nanoreactor enables collaborative precise treatment for cancer nanotherapy

Abstract: We have constructed a dual gate-controlled intelligent nanoreactor (HA-DSF@HCuS@FePtMn, HDHF) by the ingenious combination of hollow copper sulfide nanoparticles (HCuS), DSF and FePtMn nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Due to the weak acidity of the tumor microenvironment and the high concentration of hydrogen peroxide, low‐valent metal ions such as Fe 2+ , Co 2+ , Mn 2+ ions etc., and hydrogen peroxide can undergo Fenton or Fenton‐like reactions, generating highly toxic hydroxyl radicals that effectively kill cancer cells. To detect the presence of hydroxyl radicals (⋅OH), 3,3′,5,5′‐tetramethylbenzidine (TMB) was used, which reacts with ⋅OH to produce oxidized TMB with a characteristic blue color and maximum absorption peak at 652 nm [44–45] . In the presence of different concentrations of CFSDF nanocatalyst and hydrogen peroxide at pH 5.8, the UV absorbance increased with higher CFSDF nanocatalyst concentration (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the weak acidity of the tumor microenvironment and the high concentration of hydrogen peroxide, low‐valent metal ions such as Fe 2+ , Co 2+ , Mn 2+ ions etc., and hydrogen peroxide can undergo Fenton or Fenton‐like reactions, generating highly toxic hydroxyl radicals that effectively kill cancer cells. To detect the presence of hydroxyl radicals (⋅OH), 3,3′,5,5′‐tetramethylbenzidine (TMB) was used, which reacts with ⋅OH to produce oxidized TMB with a characteristic blue color and maximum absorption peak at 652 nm [44–45] . In the presence of different concentrations of CFSDF nanocatalyst and hydrogen peroxide at pH 5.8, the UV absorbance increased with higher CFSDF nanocatalyst concentration (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…To detect the presence of hydroxyl radicals ( * OH), 3,3',5,5'tetramethylbenzidine (TMB) was used, which reacts with •OH to produce oxidized TMB with a characteristic blue color and maximum absorption peak at 652 nm. [44][45] In the presence of different concentrations of CFSDF nanocatalyst and hydrogen peroxide at pH 5.8, the UV absorbance increased with higher CFSDF nanocatalyst concentration (Figure 2a). Through the TMB degradation experiment within 10 min, it was found that the absorbance at 652 nm increased with the extension of reaction time when the substance concentration was set at 100 μg/mL (Figure S10).…”
Section: A Comprehensive Study Of the Catalytic Activity And Photothe...mentioning
confidence: 99%
“…With the participation of Fe 2+ , AgNP/SWCNTs could break the O–O bond of H 2 O 2 and generate ·OH. 33 Then, the generated ·OH cleaved the DNA strand into different sequence fragments, which would peel off from the surface of AgNP/SWCNTs. Thus, a turn-on fluorescent signal could be detected whose intensity was related to the concentration of l -cysteine, illustrating that an effective method for the ultrasensitive detection of l -cysteine based on the self-cascade reaction was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that based on the peroxidase activity, AgNP/SWCNTs, especially cooperating with Fe 2+ , could catalyze the generation of ·OH derived from hydrogen peroxide. 33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation